THE DEVELOPMENT OF ISLAMIC LAW IN INDONESIA - Lina Kushidayati (P3M STAIN Kudus, 2014)
This article is a bibliographical essay of books and articles aboutthe development of Islamic law in Indonesia. Thus this paper tries oorganize some works conducted by both Indonesian and non Indonesianscholars. The article is divided into three parts. The first is introductionand then followed by the discussion about the topic itself. The secondpart is presented into several divisions according to the approaches ofstudy on the development of Islamic law in Indonesia, such as historicalapproach and legal approach. The last part is the conclusion.